2012
DOI: 10.1177/147323001204000405
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Dendritic Cells Combined with Cytokine-Induced Killer Cells Synergize Low-Dose Chemotherapy in Elderly Patients with Acute Myeloid Leukaemia

Abstract: Immuno therapy with autologous DCs and CIK cells was found to be a promising candidate for treatment of AML in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…[31] Interestingly, autologous dendritic cells plus cytokine-induced killer cells were also shown to synergize with low-dose chemotherapy [response rate (RR) of 71.4 vs. 39.1% for controls]. [32] In our elderly patient with comorbodities and high-risk cytogenetics, we gave oral metronomic induction because of the choice of the patient and based on our previous experience. [8][9][10] The combination of oral metronomic chemotherapeutic agents was not only well tolerated, but our patient also did not require any hospitalization during induction.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Interestingly, autologous dendritic cells plus cytokine-induced killer cells were also shown to synergize with low-dose chemotherapy [response rate (RR) of 71.4 vs. 39.1% for controls]. [32] In our elderly patient with comorbodities and high-risk cytogenetics, we gave oral metronomic induction because of the choice of the patient and based on our previous experience. [8][9][10] The combination of oral metronomic chemotherapeutic agents was not only well tolerated, but our patient also did not require any hospitalization during induction.…”
Section: Discussionmentioning
confidence: 99%
“…These effects include delayed-type hypersensitivity (DTH) skin test reactions, which essentially confirms the ability of the DCs to elicit T-cell-mediated immunity in vivo [52]. Other (non-specific) signs of the immunogenicity of DC therapy that have been observed include: increases in CD4 + and/or CD8 + T-cell frequencies during or after DC administration [49,53], enhanced activation of CD4 + T cells, as evidenced by their increased IFN-γ production following DC therapy [48], and elevations in plasma levels of immunostimulatory or T H 1-polarizing cytokines (such as interleukin (IL)-2) [48,49,52]. Regarding the increased IFN-γ expression, it should be mentioned that IFN-γ can in turn have an effect on DCs.…”
Section: Clinical Use Of Dcs For Immunotherapy Of Amlmentioning
confidence: 96%
“…It is also a predictive factor of imminent relapse in AML patients, including those that received allo-SCT, even when other markers are not available [70,71,72,73]. Only one study [49] reported CR and partial remissions (PR) in the relapsed/refractory setting. It is important to note, however, that these patients also received chemotherapy and CIKs, making it difficult to draw conclusions about the effectiveness of DCs as a stand-alone treatment for advanced AML.…”
Section: Clinical Use Of Dcs For Immunotherapy Of Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…(Still earlier the difference Patients from treatment group in a continued remission between LAA during AML and ALL had been demonstrated [33][34][35]). Among the methods of immunotherapy there are great hopes from the use of peptide vaccines and derivates and modifications of dendritic cells [2,[36][37][38][39][40][41], however only few of those studies are concerned with AML [42][43][44][45]. All that serves as evidence of the justifiability of searching for rational methods of immunotherapy for recovery from AL.…”
mentioning
confidence: 99%